2015
DOI: 10.1039/c5ra09959e
|View full text |Cite
|
Sign up to set email alerts
|

Egg shell membrane – a potential natural scaffold for human meniscal tissue engineering: an in vitro study

Abstract: Enhanced human primary meniscal cell proliferation in autoclaved egg shell membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…These bone‐related issues necessitate the need to increase the cellular proliferation rate of bone and associated cells for enhancing the healing, repair and tissue regeneration process. Such healing and tissue regeneration are generally accomplished using natural and synthetic scaffold structures by supporting damaged sites of bone with defined shape of interest. The scaffolds can be implanted either cell free or pre‐seeded with bone cells along with biomolecule to enhance the cell growth, attachment, proliferation and differentiation without exerting any toxic effects .…”
Section: Introductionmentioning
confidence: 99%
“…These bone‐related issues necessitate the need to increase the cellular proliferation rate of bone and associated cells for enhancing the healing, repair and tissue regeneration process. Such healing and tissue regeneration are generally accomplished using natural and synthetic scaffold structures by supporting damaged sites of bone with defined shape of interest. The scaffolds can be implanted either cell free or pre‐seeded with bone cells along with biomolecule to enhance the cell growth, attachment, proliferation and differentiation without exerting any toxic effects .…”
Section: Introductionmentioning
confidence: 99%
“…The harvested NEM was subjected to moist heat (autoclaving) and was characterized using suitable techniques. Pillai et al [48] demonstrated that autoclaved eggshell membrane can be a potential and interesting natural scaffold matrix for meniscal tissue engineering.…”
Section: Aloe Vera Gel Scaffolds With Natural (Curcumin and Eggshell mentioning
confidence: 99%
“…But the output voltage of this device was not very high and it could not achieve biocompatibility. In contrast, the biocompatibility of ESM has been reported . For example, ESM could be used as a potential natural scaffold for human meniscal, which showed increased cell adhesion and proliferation when human meniscal cells were seeded onto the fibrous side of ESM …”
Section: Introductionmentioning
confidence: 98%